Controlling your cash flow with a 1-2-3 or symphony - Glau, Gregory R. (Illinois, USA Dow Jones-Irwin, 1986)
With either 1-2-3 or symphony, the business owner has a remarkably powerful tool to track his/her cash flow.
includes bibliography and index
kjo, 01/01/2019
Loans
Keywords: Cash flow -- Computer programs